FALLS AND FEAR OF FALLING AMONG PATIENTS WITH LOWER EXTREMITY AMPUTATION - Pınar Borman,; Rıdvan Alaca,; Salim Göktepe,; Kamil Yazıcıoğlu,; Şükrü Gündüz,; Hatice Bodur, (Archives of Rheumatology, 2002)
The aim of this study was to assess the incidence of falling and fear of falling in patients with lower extremity amputees and to determine the clinical factors related with falling. Thirty-two male lower extremity amputee patients with a mean age of 25.7 ± 5.6 years were included to the study. The sociodemographic characteristics of the patients were recorded and the functional limitations were determined by modified Barthel index. The experience of falls and fear of falling of the patients were asked. The circumstances of falling including time, cause, location of falls and injury after falls were obtained and the relationship with clinical characteristics was evaluated. All the subjects had amputation for traumatic reasons. Twelve patients (37.5%) reported fear of falling and the incidence of the patients who reported falling at least once in the past year were determined as 78 %. Fifty-two % of falls occured day-time and 43.8 % occured outside of the house. Most of the patients who experienced falling, were living in the apartments. Seventeen patients injured after falls and 5 patients needed medical asistance. The incidence of falling was similar between patients who had above and below-knee amputations. Forty-four percent of patients who reported falling, had stump problems, 32 % had problems in sound leg and 76 % had pain problems in the amputed extremity. No correlation was observed between falling and fear of falling. In conclusion falling is common among lower extremity amputees. The determination of the related factors of falling and fall prevention efforts, should be emphasized in order to decrease falls and to increase the quality of life, in this group of patients.